Modulation of π-spacer of carbazole-carbazole based organic dyes toward high efficient dye-sensitized solar cells - Chirawat Chitpakdee (2018)
© 2016 Elsevier B.V. The effects of type and position of π-linker in carbazole-carbazole based dyes on their performance in dye-sensitized solar cells (DSSCs) were investigated by DFT and TDDFT methods. The calculated electronic energy level, electron density composition, charge injection and charge recombination properties were compared with those of the high performance CCT3A dye synthesized recently. It is found that that mixing a benzothiadizole (B) unit with two thiophene (T) units in the π-spacer can greatly shift absorption wavelength to near infrared region and enhance the light harvesting efficiency (LHE) resulting in increasing of short-circuit current density (Jsc), whereas a thienothiophene unit does not affect those properties. However, a B should be not directly connected to the anchoring group of the dye because it brings electrolyte to the TiO2surface which may increase charge recombination rate and consequently decrease open circuit voltage (Voc). This work shows how type and position of the π-linker affect the performance of DSSCs, and how to modulate those properties. We predicted that the designed dye derived from insertion of the B unit in between the two T units would have higher performance than CCT3A dye. The insight understanding from this study is useful for further design of higher performance dyes by molecular engineering.